2006
DOI: 10.1080/00103620600710306
|View full text |Cite
|
Sign up to set email alerts
|

Urease and Nitrification Retardation Properties in Natural Essential Oils and Their By‐products

Abstract: A laboratory incubation experiment was conducted with the natural essential oil of peppermint (Mentha spicata, MS), dementholized oil (DMO), terpenes, and a chemical inhibitor dicyandiamide (DCD), as coating materials for retardation of soil urea hydrolysis and nitrification. Retardation of nitrification was highest with DCD. The urea hydrolysis and nitrification processes were inhibited by all three natural products. Intensity of inhibition of both the processes increased with the level of application of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The PLFA profiles showed that the general microbial community composition was changed by the addition of dicyandiamide, as also found by Patra et al (2006). The PLFAs observed in the first principal component are associated with Gram negative species which would also include the nitrifying bacteria, although they represent only a very minor component of this community.…”
Section: Resultsmentioning
confidence: 85%
“…The PLFA profiles showed that the general microbial community composition was changed by the addition of dicyandiamide, as also found by Patra et al (2006). The PLFAs observed in the first principal component are associated with Gram negative species which would also include the nitrifying bacteria, although they represent only a very minor component of this community.…”
Section: Resultsmentioning
confidence: 85%
“…Neem (Azadirachta indica) products (Joseph and Prasad 1993;Kumar et al 2007) and plant oils (Erickson et al 2000;Patra et al 2006) have been shown to be as effective as synthetic inhibitors. However, difficulties with consistent delivery of the active ingredient in quantities that ensure the inhibitor is present in soils for long enough to provide sufficient control of nitrification are likely to restrict wide use.…”
Section: Production Of Nitrification Inhibitors By Plant?mentioning
confidence: 99%
“…For example, neem (Azadirachta indica A. Juss), karanja (Pongamia glabra Vent)-products (Parmar et al 1976; and certain plant oils (Patra et al 2006) have been reported to show inhibitory effect on soil nitrification. In most cases, the active chemical constituents were either undefined or there were difficulties with consistent delivery of active ingredients in sufficient quantities to maintain inhibition; consequently they have had only limited value in production agriculture (Fillery 2007).…”
Section: Introductionmentioning
confidence: 98%